The Assessment of Postural-Motor, Coordination, and Reflex Functions in Children and Adolescents with a History of Premature Verticalization and Ontogeny Disorders in Their First Year of Life - Mieczysław Maciak; Kamil Koszela; Anna Beniuk; Marta Woldańska-Okońska (MDPI AG, 2024)
(1) Background: Contracting diseases or being exposed to adverse environmental factors in the first year of life may impair the development of body posture and motor coordination. The purpose of this study was to evaluate the correlation between data on the speed of passive verticalization, the number of risk factors and the quality of development in the first year of life, and the results of the functional examination of these individuals in adolescence. (2) Methods: Two groups of 60 volunteers, aged 9-14 years, were examined by performing functional tests and the retrospective analysis of their development up to the age of 1 year. The first group consisted of patients diagnosed with postural defects. The control group consisted of healthy people of the same age who volunteered for this study. (3) Results: Statistical analysis showed statistically significant differences between groups in terms of posture (p = 0.001), motor coordination (p = 0.001), and accumulated primitive reflexes (p = 0.001), as well as a high correlation between these disorders and the quality of development in the first year of life. In the first group, for the ages of 3-6 months (r = 0.96; p = 0.001), 6-9 months (r = 0.871; p = 0.001), and 9-12 months (r = 0.806; p = 0.001), no significant correlations were found with the age of 0-3 months. In the second group, the results were as follows: 0-3 months (r = 0.748; p = 0.001), 3-6 months (r = 0.862 p = 0.001), 6-9 months (r = 0.698; p = 0.001), and 9-12 months (r = 0.740; p = 0.001). In the group of adolescents with posture defects, we observed an earlier time of passive verticalization and sitting, as well as more frequent use of loungers, seats, and walkers (p = 0.026). (4) Conclusions: The analysis of this study's data indicates that the development of body posture and motor coordination may be impaired due to accelerated and passive verticalization in the first year of life.